Tackling the global burden of cancers - Borodo, M. M. (Nigerian Journal of Basic and Clinical Sciences, 2026)
Cancers continue to be a major cause of mortality, morbidity and disability‑adjusted life years (DALYs), the world over. The regional variations occur not only by virtue of cancer type and presentation, risk factors and opportunity for prevention, control and treatment, but also by the availability of healthcare resources as well as the level of health education in the regions. In 2000 alone, 5.3 million males and 4.7 million females worldwide developed cancers with a total of 6.2 million deaths. Currently 12% of global mortality is from cancers and 70% of the global cancer burden is found in low‑ to medium‑income countries. Furthermore, based on the current trends of the risk factors and risk behaviours for cancers globally, which is expected to increase by 50% in the next decade, it is estimated that the incidence of cancers would rise to 15 million people by the year 2020. In 2008 alone, based on a systematic analysis of DALYs on global burden of cancers, Soerjomataram and colleagues estimated that worldwide 168 million years of healthy life were lost due to cancers with an individual loosing, on average, 2 years of healthy life after cancer diagnosis.[1] The authors further noted that colorectal, lung, breast and prostate cancers were the main contributors to the total DALYS in most regions of the world, accounting for 18‑50% of the total global burden for cancer. In sub‑Saharan Africa and East Asia, an additional large burden from infection‑related cancers (hepatocellular, gastric and cervical cancers) was estimated at 25% and 27%, respectively.